2016
DOI: 10.1111/jace.14387
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Effects in Perovskite Ferroelectrics: Fundamental Limits and Process‐Structure‐Property Relations

Abstract: Ferroelectric materials are well‐suited for a variety of applications because they can offer a combination of high performance and scaled integration. Examples of note include piezoelectrics to transform between electrical and mechanical energies, capacitors used to store charge, electro‐optic devices, and nonvolatile memory storage. Accordingly, they are widely used as sensors, actuators, energy storage, and memory components, ultrasonic devices, and in consumer electronics products. Because these functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
112
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(113 citation statements)
references
References 269 publications
(649 reference statements)
1
112
0
Order By: Relevance
“…However, there is little understanding of how the as‐grown amorphous films crystallize during post‐deposition heat treatment, which is required for ALD‐grown BFO films. In particular, for polycrystalline films both, composition and microstructure, have tremendous effects on the resulting properties …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is little understanding of how the as‐grown amorphous films crystallize during post‐deposition heat treatment, which is required for ALD‐grown BFO films. In particular, for polycrystalline films both, composition and microstructure, have tremendous effects on the resulting properties …”
Section: Resultsmentioning
confidence: 99%
“…In particular, for polycrystalline films both, composition [26] and microstructure, have tremendous effects on the resulting properties. [27] In this report, we provideadetailed investigation of the crystallization of Bi-Fe-Of ilms grown via as uperlattice approach.H erein, semi-amorphous Fe 2 O 3 -Bi 2 O 3 superlattices were studied by in situ X-ray diffraction (XRD) and X-ray reflectivity (XRR), in situ X-ray photoelectron spectroscopy (XPS), scanning transmission electronm icroscopy( STEM) and transmission electron microscopy (TEM) after annealing at selected temperatures (T). In addition, we present piezoresponse force microscopy (PFM) results obtained on ap olycrystalline BFO film.…”
mentioning
confidence: 99%
“…These design goals are, in principle, achievable via thickness reduction in the ferroelectric. However, it is widely reported that the functional properties of ferroelectric films are strongly thickness dependent, reducing concomitantly with film thickness …”
Section: Introductionmentioning
confidence: 99%
“…Discontinuity at the crystallization interfaces, both in the grain/domain structure and crystallite orientation are readily visible in the TEM analyses ( Figure 4B,C,E). 36,37 In smaller grains where smaller domains are expected, domain walls are bound to exhibit reduced mobility, due to greater chances of interaction with other defects, including grain boundaries and domain walls-potentially resulting in diminished extrinsic contributions to the dielectric response. This observation is important since these discontinuities in the MLA film suggest that the density of such interfaces and the number of anneals can have a substantial impact on the crystallography throughout the film thickness, and hence the overall functional properties of the film.…”
Section: Discussionmentioning
confidence: 99%